2021
DOI: 10.3390/bioengineering8110167
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Macrophage Activity by Pulsed Electromagnetic Fields in the Context of Fracture Healing

Abstract: Delayed fracture healing and fracture non-unions impose an enormous burden on individuals and society. Successful healing requires tight communication between immune cells and bone cells. Macrophages can be found in all healing phases. Due to their high plasticity and long life span, they represent good target cells for modulation. In the past, extremely low frequency pulsed electromagnet fields (ELF-PEMFs) have been shown to exert cell-specific effects depending on the field conditions. Thus, the aim was to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 58 publications
(100 reference statements)
1
16
0
1
Order By: Relevance
“…The electrophoresis was carried out at 90 V for 60 min to separate the PCR products. Finally, the intensity of the bands was quantitatively analyzed by ImageJ (NIH, Bethesda, MD, USA) [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrophoresis was carried out at 90 V for 60 min to separate the PCR products. Finally, the intensity of the bands was quantitatively analyzed by ImageJ (NIH, Bethesda, MD, USA) [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…The protein concentrations were determined with the micro-Lowry method [ 15 ]. As previously described [ 47 ], 25 μg of total protein was separated by 12% acrylamide gels (100 V, 180 min) and then transferred onto a nitrocellulose blotting membrane (100 mA, 180 min). Ponceaus staining was used to visually ensure adequate protein transfer.…”
Section: Methodsmentioning
confidence: 99%
“…As a further verification of the ability of our system to provide biologically relevant and well-controlled exposures to cell cultures, we tested two additional short-pulsed signals E and F (CIT#81 and CIT#96), which were featured in studies of [ 54 , 56 ]. With Signal E ( Figure 5 E, CIT#81), we showed that a signal with in the -range ( s) is also able to significantly decrease the inflammatory response in HEK-Blue™ hTLR4 cells by roughly .…”
Section: Resultsmentioning
confidence: 99%
“…For Figure 2 C,D, the duty cycle has been adjusted so that equals that of signal B and A, respectively, see Table 2 . In addition, we used two PEMF signals with a proprietary, monopolar, triangular shape and a short pulse length s (so-called CIT-pulse [ 21 , 56 ]).…”
Section: Methodsmentioning
confidence: 99%
“…В этих условиях показана возможность супрессора цитокиновой сигнализации SOCS2 модулировать активность JAK/STAT-сигнального пути и ядерного фактора транскрипции NF-κB, регулируя тем самым провоспалительную реактивность ИКК и их чувствительность к цитокинам. При этом противовоспалительное действие SOCS2, очевидно определяющееся его влиянием на уровень отдельных компонентов ядерного фактора транскрипции NF-κB, сочетается с иммунорегулирующим влиянием, выражающимся в изменении фосфорилирования отдельных STAT-факторов, что, в свою очередь, определяет изменение чувствительности ИКК к цитокинам и формирование стимулов к дифференциации и пролиферации соответствующих популяций ИКК, включая Т-хелперы [9-12, 16, 17] Таким образом, полученные в настоящем исследовании данные, в том числе, свидетельствующие о важной роли JAK/STAT-сигнального пути, а также баланса SOCS2/STAT3 в регуляции саногенеза у реконвалесцентов ВП, позволяют считать указанные факторы потенциальными терапевтическими мишенями, воздействие на которые способно обеспечить усиление активности процессов саногенеза, а также восстановление нарушенной иммунологической реактивности на этапе реабилитации больных, перенесших пневмонию [14,[20][21][22]. При этом очевидно, что восстановление у реконвалесцентов ВП исходной реактивности ИКК определяет нормальное восстановление процессов репарации и регенерации тканей, а также является фактором препятствующих развитию повторных инфекционных заболеваний, в том числе, повторных пневмоний, а также суперинфекций [17].…”
Section: обсуждение результатов исследованияunclassified